2000
DOI: 10.1002/1097-4628(20000801)77:5<982::aid-app4>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Radiation processing of polyolefin blends. I. Crosslinking of EPDM-PP blends

Abstract: Radiation crosslinking of polymer blends containing the ethylene–propylene terpolymer (EPDM) and polypropylene (PP) was studied. Four binary systems with mixing ratios of 80/20, 60/40, 40/60, and 20/80 w/w and the individual components were γ‐processed. The development of the gel content formed in irradiated blends proved that the increase in PP concentration generated an increasing insoluble fraction. A linear dependence of the gel fraction on PP concentration was found. The optimal dose range for the efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Zaharescu and his colleagues have shown that at doses from 40 or 50 up to 200 kGy there can be significant cross-linking [2,10,11]. We recall that our samples were irradiated following an ASTM standard, between 18 and 30 kGy, hence below the Zaharescu threshold.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Zaharescu and his colleagues have shown that at doses from 40 or 50 up to 200 kGy there can be significant cross-linking [2,10,11]. We recall that our samples were irradiated following an ASTM standard, between 18 and 30 kGy, hence below the Zaharescu threshold.…”
Section: Resultsmentioning
confidence: 89%
“…There has been a rapid rise in the use of polymer-based materials in medical applications ranging from drug-delivery systems to medical devices [1][2][3]. In particular, thermoplastic vulcanizate elastomers (TPVs) have found use in medical devices and implants due to their excellent combination of properties and processability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the two effects, crosslinking and degradation, coexist and we need to point out the predominance of one of them. In addition, through appropriate surface treatments, some features of the feet such as appearance, adhesion to different materials or slip resistance can be significantly improved (Zaharescu, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Variables such as radiation dosage and the effect of polymer microstructure and chemical additives on the efficiency of electron beam cure have been studied. Some researchers (Zaharescu et al, 2000;Chowdhury & Banerji, 2005) studied radiation-induced crosslinking in thermoplastic elastomers based on ethylene-propylene rubber (EPDM) and polyethylene (PE) or polypropylene (PP) plastics.…”
Section: Electron Beam and Microwaves Vulcanizationmentioning
confidence: 99%